Prevalence of uterine synechia after abortion evacuation curettage - Salzani, Adriana; Yela, Daniela Angerame; Gabiatti, José Roberto Erbolato; Bedone, Aloísio José; Monteiro, Ilza Maria Urbano (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Intrauterine adhesion (IUA) is a possible complication of uterine curettage following abortion. Because IUA is an important cause of infertility, some investigators have been advocating its inclusion in the routine investigational workup after every abortion curettage procedure. The aim of this study was to evaluate the uterine cavity of patients subjected to abortion curettage, in order to ascertain the prevalence of IUA and its association with social and clinical factors. DESIGN AND SETTING: This was a cross-sectional study at the Human Reproduction Unit, Department of Obstetrics and Gynecology, Universidade Estadual de Campinas (Unicamp). METHODS: A total of 109 women were enrolled. The investigators searched the records of Unicamp’s hospital for patients who had been subjected to uterine curettage following abortion. The hysteroscopy was performed 3 to 12 months after the curettage. The correlations between patients’ characteristics and the prevalence of IUA were assessed by means of chi-squared and Fisher’s exact test calculations. RESULTS: The prevalence of IUA was 37.6%. The number of previous abortions and curettage procedures did not correlate with the presence of IUA. Most of the women (56.1%) presented IUA grade I. CONCLUSIONS: In the present study, 37.6% of the women subjected to curettage following abortion had IUA, which was mostly mucous and grade I. None of the demographic and clinic characteristics evaluated were found to be associated with IUA. From this study, there is no fi rm evidence to justify carrying out routine diagnostic hysteroscopy following abortion evacuation.